Harmony of Relations between Religious People and Conflict Resolution in Kediri - Dodi, Limas (ADDIN, 2022)
Conflicts between religions and religious sects in several parts of Indonesia are still an actual issue and a resolution formulation is still being sought. This paper seeks to reveal the social reality of religious harmony and inter-religious diversity in Kediri, East Java, Indonesia. This research is based on field data by releasing all the opinions of researchers in revealing facts and reality, the researchers propose a pattern of assumptions according to the developed hypothesis. Informants come from several people who have different religious backgrounds. This paper concludes: First, the model of religious harmony and, the same religion in Kediri City is intertwined by compromising character, culture, the authority like scientific profession. Interaction of religious communities is built through the theological-social concept, namely upholding religious principles. Second, socio-religious analysis confirmed that the phenomenon of religious harmony in the city of Kediri. The informants view that religion is right as a social controller that is dynamic and tolerant. Religion is outside the social layer as a fundamental value, that is, as the principle that God wants peace and humans are the same. The socio-religious sub-system is built by authority holders such as religious leaders, intellectuals, prophets, scholars, and the government.